A Combined Sodium Intercalation and Copper Extrusion Mechanism in the Thiophosphate Family: CuCrP2S6 as Anode Material in Sodium‐Ion Batteries. Issue 11 (2nd May 2022) - van Dinter, Jonas; Grantz, David; Bitter, Alexander; Bensch, Wolfgang
Abstract: The layered hypothiophosphate CuCrP2 S6 was identified as promising candidate for the application as anode in sodium‐ion batteries exhibiting an appropriate electrochemical performance (409 mAh g −1 after 200 cycles @ 1 A g −1 ). The electrochemical long‐term experiments suggest that the reaction mechanism changed upon repeated discharging and charging. The initial discharge and charge process was studied by X‐ray diffraction evidencing that at the early discharge stages, Na + was intercalated into the interlayer space accompanied by a simultaneous reduction of Cu + to metallic Cu, which was extruded from the host. At later stages of discharge, a conversion of the intermediate phase to Cu 0, amorphous Cr 0 and P 0 embedded in nanocrystalline Na2 S occurred. After recharging, only reflections of nanocrystalline NaF could be identified, which is part of the generated solid electrolyte interphase (SEI) layer. In contrast to observation made in literature, elemental Cu seems to be oxidized during the charge process again. Abstract : Combined intercalation‐reduction‐extrusion : a very rare reaction mechanism was demonstrated. In the first step, Na + ions were intercalated into the layered structure. After the interlayer space was completely occupied, the insertion of Na + ions continued and was accompanied by reduction of Cu + ions, which were then expelled from their sites within the van‐der‐Waals layer resulting in the deposit of elemental Cu.